Application of dolomite as solid base catalyst for transesterification of rapeseed oil with butanol. (August 2022) - Gaide, Ieva; Makareviciene, Violeta; Sendzikiene, Egle; Gumbyte, Milda
Graphical abstract: Highlights: Butanol was used for transesterification of rapeseed oil. Influence of four independent variables on the process efficiency was investigated. RSM was used for process optimization. Physical and chemical properties of produced biodiesel were determined. Abstract: The article presents the results of studies on the transesterification of rapeseed oil with butanol using a heterogeneous catalyst (0.315–0.1 mm) of the dolomite calcined at 850 °C. Experimental plan was prepared and results analyzed using response surface methodology. Interaction of four independent variables were analyzed and presented in the article. It was found that the biggest influence on ester yield have the temperature and the duration of the reaction. After optimizing the process, it was found that in 8 h the highest ester yield of 94.55 wt% is obtained using 5.24 wt% of dolomite, at 110 °C and 13.71:1 M ratio of butanol to oil.